PENGEMBANGAN INSTRUMEN PENILAIAN HIGHER ORDER THINKING SKILLS (HOTS) PADA MATERI ZAT ADITIF - Saleha, Tsaniya Rahma; Muharini, Rini; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe aims of this research were to know how the feasibility and how teachers’s response on the Higher Order Thinking Skills (HOTS) assessment instrument on the aditif substance material. The form of this research was  research and development (R&D) with Borg and Gall developing model which had been simplified by Puslitjaknov team into 5 main phases. HOTS assessment instrument being developed consisted of HOTS  grids sheets problem in the form of essay, and HOTS scoring guidances (features) instrument. The  validated HOTS assessment instrument was tried out to the science teachers at SMPN 10 Pontianak, SMPN 12 Pontianak, and SMPN 16 Pontianak.The result of feasibility of HOTS assessment instrument was 93.72 %  which has high feasibility in the criterion so it was categorized very feasible used in the teaching learning process. The result of the teachers’s response questionnaring on the HOTS assessment instrument was 97.02 % which was very high in the criterion so it showed that teachers’s response on the HOTS assessment instrument was very good. Keywords:  Assessment Instrument, Higher Order Thinking Skills (HOTS), Aditif Substance